Effect of methimazole treatment on Th1, Th17, and Th22 lymphocytes in pediatric Graves’ disease patients - Starosz, Aleksandra; Stożek, Karolina; Opęchowska, Aleksandra; Bossowski, Filip; Moniuszko, Marcin; Grubczak, Kamil; Bossowski, Artur (Frontiers in Immunology, 2024)
Graves's disease is the leading cause of autoimmune hyperthyroidism. Thyroid hormones are an essential element of the endocrine system, playing a pivotal role in the body's development, especially important in children with intensified growth. Disturbance within thyroid tissue certainly affected the whole body. Nowadays, numerous research studies indicate different factors contributing to the onset of the disease; however, the exact pathomechanism of Graves' disease is still not fully understood, especially in the context of immune-related processes. Th1, Th17, and Th22 effector lymphocytes were found to be crucial participants in the disease outcome, as well as in autoimmune diseases. Here, our study aimed at assessing selected effector T lymphocytes, Th1, Th17, and Th22, in newly diagnosed Graves' pediatric patients, together with their association with thyroid-related parameters and potential outcome of disease management. We indicated significant increases in the frequencies and absolute numbers of selected effector lymphocytes in Graves' disease patients. Also, their mutual ratios, as well as Th1/Th17, Th/Th22, and Th17/Th22, seem to be found as significant in those diseases. Notably, low Th17/Th22 ratio values were distinguished as potential prognostic factors for normalizing TSH levels in response to the methimazole treatment. To sum up, our research determines a crucial contribution of Th1, Th17, and Th22 cells in the pathogenesis of Graves'' disease. Moreover, the mentioned subset of T cells is highly likely to play a substantial role in the potential prediction of therapy outcomes.